The THE ROLE OF THE ENVIRONMENT SERVICE IN CREATING A CLEAN CITY IN WAMENA CITY - TATI HARYATI (Program Studi Pendidikan Kependudukan dan Lingkungan Hidup, 2021)
Wamena City or Baliem Valley is a unique city located in a mountainous area that is being hunted by foreign tourists. However, the threat of environmental pollution due to waste has become a threat to the innovation policy of the Regional Government of Jayawijaya Regency. Therefore, it is hoped that the Jayawijaya Regency Regional Government will have an active role in this case the Jayawijaya Regency Environmental Service which is of course responsible for the Environmental Cleanliness of Wamena City. Through a qualitative method, the authors found that the lack of facilities provided by the Jayawijaya Regency Government made it difficult to realize a Clean Wamena City, in addition, which was marked by the behavior of people who were still not aware of the importance of maintaining cleanliness, littering, or the presence of a lot of piles. garbage that can be found everywhere, there is not even a clear sanction for each violator.